Single Nucleotide Polymorphism of ADIPOQ Gene (Rs822393) Is Associated with Lipid Profile, Adiponectin Levels and Ratio of Adiponectin/Leptin ratio in Adult Obese Subjects - Luis, Daniel de; Izaola, Olatz; Primo, David; Aller, Rocio (Cardiology and Cardiovascular Medicine, 2021)
Objectives: Some studies in the literature indicate that ADIPOQ rs822393 polymorphism functionally regulates adiponectin levels. The aim of this study was to describe the association of rs822393 with adiponectin levels, cardiovascular risk factors, diabetes mellitus type 2 and metabolic syndrome. Patients and Methods: The study involved a population of 1004 Caucasian adult obese subjects. Anthropometric parameters, blood pressure, fasting blood glucose, C-reactive protein (CRP), insulin concentration, insulin resistance (HOMA-IR), lipid profile, adipokines levels, ratio adiponectin/leptin ratio and prevalence of MS were recorded. Genotype of ADIPOQ gene polymorphism (rs822393) was evaluated. Results: The distribution of the rs822393 polymorphism in this adult population was 62.1% (n=623) (CC), 32.1% (n=322) (CT) and 5.8% (n=59) (TT). We observed an association between the minor T allele and lower HDL cholesterol levels (CC vs. CT+TT: delta: 6.6+1.2 mg/ml;p=0.03) and lower adiponectin levels (CC vs. CT+TT: delta: 19.9+3.2 mg/ml;p=0.02). T allele carriers showed lower adiponectin/leptin ratio (CC vs. CT+TT: delta: 0.29+0.1 mg/ml;p=0.02) than non T allele carriers. Logistic regression showed that the T allele increased the risk of low HDL cholesterol (OR=2.75, 95% CI=1.87-4.02, p=0.03), after adjusting by BMI and age.